STRATEGI BRANDING DAN PEMASARAN ONLINE PADA UMKM RUMAHAN RT 05/01 DESA PANONGAN, KECAMATAN PANONGAN, KABUPATEN TANGERANG, BANTEN - Arfan; Agistiawati, Eva; Mariyanah, Siti; Rahmawati, Yunita; Taro, Mazdhalifah; Kurniawan, Muhammad Arif; Fuadi, Aris; Wahid, Abdul; Simorangkir, Yosua Novembrianto; Rukmana, Andi; Prabowo, Anto; Widjiyanta; Sadewo, Tatang Iman; Sasono, Ipang; Johan, Muhammad; Fajriyah, Nurul; Suseno, Bayu; Nugroho, Pratomo Djati; Kabir, Abdul; Fitri, Aminul; Purnama, Desi; Saputra, Aldo Aly; Raisayah, Zahra Atikah (LPPM Universitas Insan Pembangunan, 2026)
Micro, Small, and Medium Enterprises (UMKM) play a vital role in improving the community's economy and family well-being. However, many home-based UMKM still face challenges in product branding, digital marketing, utilizing digital platforms, and expanding market reach, including UMKM at Green Panongan Residence, RT 05/01, Panongan Village, Panongan District, most of whom still rely on conventional marketing and lack a strong brand identity. This Community Service (PKM) activity aims to improve the knowledge and skills of UMKM in implementing branding and online marketing strategies to increase business competitiveness. The methods used included observation, identifying partner needs, interactive lectures, guided practice based on artificial intelligence (AI), and ongoing mentoring on brand identity development, business social media management, and digital platform utilization. The activity was held on June 16, 2026, and was attended by 90 participants. The results showed an increased understanding of the importance of brand identity, the use of digital media for promotion, and a shift in mindset from conventional marketing to the use of digital technology. This program supports community economic empowerment and strengthens the capacity of business actors to face the challenges of the digital era.